2004
DOI: 10.1254/jphs.94.129
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Effects of Astaxanthin Combined With Ginkgolide B on T Lymphocyte Activation in Peripheral Blood Mononuclear Cells From Asthmatic Subjects

Abstract: Abstract. This study was undertaken to identify novel approaches to pharmacological treatment of asthma. Here we hypothesize that the platelet-activating factor receptor antagonist ginkgolide B (GB) in combination with the antioxidant carotenoid astaxanthin (ASX) suppresses T cell activation comparably to two commonly-used antihistamines: cetirizine dihydrochloride (CTZ) and azelastine (AZE). Peripheral blood mononuclear cells from asthmatics, cultured 24 h with either 50 mg / ml phytohemaglutinin (PHA) or PHA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Ginkgolide B, the major bioactive component of G. biloba extracts, has been reported to play multiple pharmacological roles as mentioned above (11,14,19,21,38,40). Recent studies have found that ginkgolide B may have anticancer properties in molecular, cellular, and whole animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Ginkgolide B, the major bioactive component of G. biloba extracts, has been reported to play multiple pharmacological roles as mentioned above (11,14,19,21,38,40). Recent studies have found that ginkgolide B may have anticancer properties in molecular, cellular, and whole animal models.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that that ginkgolide B, astaxanthin, or their combination could suppress activation of T cells from asthma patients [38]. In the recent experiment, Haines et al [39] showed that the asthmatic animals fed astaxanthin, Ginkgo biloba extract and vitamin C alone or in combination exhibited significantly lower bronchoalveolar lavage fluid inflammatory cell numbers and enhancement of lung tissue content of cAMP and cGMP, and the efficacy was equal to or better than ibuprofen, a widely used nonsteroidal antiinflammatory drug.…”
Section: Anti-inflammatory Effectsmentioning
confidence: 99%
“…Recently, further functionalities of astaxanthin in addition to its antioxidative ability have also been reported, including anti-cancer, 5,6) prevention of diabetic nephropathy, 7) prevention of H. pylori infection, 8) alleviation of eye fatigue, 9) and immunomodulating ability. 10,11) Absorption of xanthophylls is believed to occur as follows: After ingestion, xanthophylls mix with bile acid to make micelles in the intestinum tenue. Next, the micelles containing xanthophylls are passively absorbed by intestinal mucosal cells.…”
mentioning
confidence: 99%